Modeling bipolar phase-shifted multielectrode catheter ablation - Tungjitkusolmun, Supan; Haemmerich, Dieter; Cao, Hong; Tsai, Jang Zern; Choy, Young Bin; Vorperian, Vicken R.; Webster, John G. (My University, 2002)
Atrial fibrillation (AFIB) is a common clinical problem affecting approximately 0.5-1% of the United States population. Radio-frequency (RF) multielectrode catheter (MEC) ablation has successes in curing AFIB. We utilized finite-element method analysis to determine the myocardial temperature distribution after 30 s, 80 °C temperature-controlled unipolar ablation using three 7F 12.5-mm electrodes with 2-mm interelectrode spacing MEC. Numerical results demonstrated that cold spots occurred at the edges of the middle electrode and hot spots at the side electrodes. We introduced the bipolar phase-shifted technique for RF energy delivery of MEC ablation. We determined the optimal phase-shift (φ) between the two sinusoidal voltage sources of a simplified two-dimensional finite-element model. At the optimal φ, we can achieve a temperature distribution that minimizes the difference between temperatures at electrode edges. We also studied the effects of myocardial electric conductivity (σ), thermal conductivity (κ), and the electrode spacing on the optimal φ. When we varied σ and κ from 50% to 150%, optimal φ ranged from 29.5° to 23.5°, and in the vicinity of 26.5°, respectively. The optimal φ for 3-mm spacing MEC was 30.5°. We show the design of a simplified bipolar phase-shifted MEC ablation system.
Keywords: Bipolar ablation; Cardiac ablation; Catheter ablation; Finite-element; Phase-shift; Radiofrequency ablation